Endocardial left ventricular pacing Where are we a systematic review. (24th May 2021) - Santos, H; Santos, M; Almeida, I; Paula, S; Miranda, H; Figueiredo, M; Neto, M; Sa, C; Sousa, C; Chin, J; Almeida, S; Almeida, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Endocardial left ventricular pacing is a technique used in cardiac resynchronization therapy (CRT), when a coronary sinus implant is not possible, conventional CRT was an unsuccess and in CRT nonresponders. We performed a systemic review to evaluate its risks and benefits. Objective: Review the evidence regarding the efficacy and safety of endocardial left ventricular pacing. Methods: A systemic research on MEDLINE and PUBMED with the term "endocardial left ventricular pacing", "biventricular pacing" or "endocardial left pacing". 1038 results were identified, however, just publish papers (excluding abstract) with more than 16 patients was admitted in these analyses. Comparisons pre and post CRT regard New York Heart Association (NYHA) functional classification, left ventricular ejection fraction (LVEF) and QRS width was performed. Mean differences (MD) and confidence interval (CI) was used as a measurement of treatment. Results: Eleven studies were selected, including a total of 560 patients. The studies were performed with different techniques, trans-atrial septal technique, trans-ventricular septal technique and transapical technique. Mean age 66.93 years old, 90.54% male, median ejection fraction of 28.86%, NYHA class of 3.03, QRS width 167, 50 mseg. Ischemic etiologic in 43.88%, atrial fibrillation in 45.35% and left bundle branch block in 55.20%. Was reported several complications after the procedure, 8 pocket infection (7 studies), 17 transient ischemic attacks (10 papers), 17 ischemic stroke (all), 35 tromboembolic events (all) and 115 deaths, nevertheless, follow up in the different studies was diverse and heterogeneous. Significant improvement was registered in NYHA class (MD 0.64, CI 0.56-0.72, p < 0.00001, I2 = 89%) (reported in 7 studies), LVEF (MD 6.20, CI 5.09-7.32, p = 0.002, I2 = 69%) %) (reported in 8 studies) and QRS width (MD 31.35, CI 26.11-36.60, p < 0.00001, I2 = 89%) %) (reported in 5 studies), (all p < 0.00001). Conclusions: Left ventricular endocardial pacing is a feasible alternative to conventional CRT, when the last one is not possible. With clinical, electrocardiogram and echocardiogram improvement in several series. First data regarding this procedure were associated with higher stroke incidence, something contrary to the last study's results. Nevertheless, at the moment just small series present this technique with heterogenous results and different approaches, being important further investigation.